Drosophila Heart as a Model for Cardiac Development and Diseases. - Souidi, A.; Jagla, K. (Cells, 2021)
The Drosophila heart, also referred to as the dorsal vessel, pumps the insect blood, the hemolymph. The bilateral heart primordia develop from the most dorsally located mesodermal cells, migrate coordinately, and fuse to form the cardiac tube. Though much simpler, the fruit fly heart displays several developmental and functional similarities to the vertebrate heart and, as we discuss here, represents an attractive model system for dissecting mechanisms of cardiac aging and heart failure and identifying genes causing congenital heart diseases. Fast imaging technologies allow for the characterization of heartbeat parameters in the adult fly and there is growing evidence that cardiac dysfunction in human diseases could be reproduced and analyzed in Drosophila, as discussed here for heart defects associated with the myotonic dystrophy type 1. Overall, the power of genetics and unsuspected conservation of genes and pathways puts Drosophila at the heart of fundamental and applied cardiac research.